PENGARUH BENTUK-BENTUK LATIHAN KELINCAHAN TERHADAP KEMAMPUAN FOOTWORK ATLET BULUTANGKIS PB. NADA JUNIOR KERINCI - Yuda Pratama (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Problems in research is achievement atletnya decline .Research purposes to to know whether is the exercise forms agility of the ability of footwork athletes badminton PB. NADA Junior Kerinci . This research is apparent experimental namely providing treatment of athletes badminton PB. NADA Junior Kerinci .For research these are using the control group , but this study are part apparent experiment .The population of the research is an athlete badminton PB. NADA Junior Kerinci , there are 17 people. Engineering the sample is purposive sampling .Because technique sample of sampling this determines with certain consideration seen can provide data in full , then made sample population as many as 12 people .Data analyzed by a formula statistics “t-test” The results in research is as follows: test t between the influence of forms of the ability of exercise agility footwork thit 5.51 to ttab the first significant α = 0.05 namely 2.20 .Means in this is the that means between forms of the ability of exercise agility footwork athletes badminton PB. NADA Junior Kerinci.